2017
DOI: 10.1002/cncr.30939
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time to initiation of postoperative radiation therapy on survival in surgically managed head and neck cancer

Abstract: Background Determine the effect of National Comprehensive Cancer Network Guideline- adherent initiation of postoperative radiation therapy (PORT), and different time to PORT intervals, on overall survival (OS) in patients with head and neck squamous cell carcinoma (HNSCC). Methods Reviewing the National Cancer Database (NCDB) from 2006–2014, patients with HNSCC undergoing surgery and PORT were identified. Kaplan-Meier survival estimates, Cox regression analysis, and propensity score matching were used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
186
4
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 125 publications
(206 citation statements)
references
References 35 publications
10
186
4
6
Order By: Relevance
“…14,15,19,20,30 All were published in 2017 or later and set in the United States. Four studies 14,15,20,30 used cancer registry data and 1 study 19 used a single institution design. Four studies 14,15,19,20 found an association between delays in the S-PORT interval and poorer oncologic outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15,19,20,30 All were published in 2017 or later and set in the United States. Four studies 14,15,20,30 used cancer registry data and 1 study 19 used a single institution design. Four studies 14,15,19,20 found an association between delays in the S-PORT interval and poorer oncologic outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies 14,15,20,30 used cancer registry data and 1 study 19 used a single institution design. Four studies 14,15,19,20 found an association between delays in the S-PORT interval and poorer oncologic outcomes. The only study that did not find an association between timely S-PORT and survival used study cohort quartiles to define delayed PORT (≥ 64 days vs <50 days) 30 instead of National Comprehensive Cancer Network Guideline recommendations (≤ 6 weeks vs >6 weeks).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Delays in timely care are a source of preventable mortality and a contributor to racial disparities in outcomes. 15,21,22,29 …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, delays in initiation of PORT are common 14,16 and associated with decreased survival. 19,21 These delays, which disproportionately affect racial minorities, 16 contribute to racial disparities in HNSCC outcomes. 22 …”
mentioning
confidence: 99%